A Highly Stretchable Cross‐Linked Polyacrylamide Hydrogel as an Effective Binder for Silicon and Sulfur Electrodes toward Durable Lithium‐Ion Storage. (17th January 2018) - Zhu, Xingyu; Zhang, Fei; Zhang, Li; Zhang, Liya; Song, Yingze; Jiang, Tao; Sayed, Shah; Lu, Chen; Wang, Xiangguo; Sun, Jingyu; Liu, Zhongfan
Abstract: Despite the recent advancement in the in‐practical active materials (e.g., silicon, sulfur) in the rechargeable lithium‐ion energy storage systems, daunting challenges still remain for these high‐capacity electrode material candidates to overcome the severe volume changes associated with the repeated lithiation/delithiation process. Herein, developing a room‐temperature covalently cross‐linked polyacrylamide (c‐PAM) binder with high stretchability and abundant polar groups targeting the construction of high‐performance Si and sulfur electrodes is focused on. The robust 3D c‐PAM binder network enables not only significant enhancement of the strain resistance for working electrodes but also strong affinity to bonding with nano‐Si surface as well as effective capture of the soluble Li2 S n intermediates, thereby giving rise to remarkably improved cycling performances in both types of electrodes. This rational design of such an effective and multifunctional binder offers a pathway toward advanced energy storage implementations. Abstract : A covalently cross‐linked polyacrylamide hydrogel with high stretchability and abundant polar groups is utilized as binder material for fabricating high‐strength silicon and sulfur electrodes. Such a multifunctional binder can provide strong affinity to bonding with the nanosilicon surface and trap the soluble polysulfide intermediates, resulting in remarkably improved electrochemical performance of both the silicon anodes and sulfur cathodes.